FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL (Students' Journal of Accounting and Banking, 2013)
This research aims to test the influence of company size, business risk, liquidity and profitability of capital structure in listed companies in BEI. Some previous research on capital structure shows different results. Therefore the research needs to be done to analyze the theory of capital structure. The Data used is the manufacturing company listed in BEI 2007-2011. Research using a purposive sampling and sample as many as 69 research data. Research Data are then tested by multiple linear regression analysis to test the influence of company size, business risk, liquidity, and profitability of capital structure. The results of this study indicate that the size of the company positively and not significant, business risk positively and not significant, liquidity negative effect  and significant, and profitability negative effect  and significant of capital structureKeywords : Size,Business Risk, liquidity, Profitability, and Capital Structur